HUBUNGAN TINGKAT PENDAPATAN KELUARGA DAN POLA MAKAN DENGAN STATUS GIZI BALITA - Nur Ilmi Masnur; M. Rachmat Kasmad; Poppy Elisano Arfanda; Nurfaidah Nurfaidah; Kartini Kartini (JOURNAL HEALTH AND NUTRITIONS, 2026)
Nutritional status of toddlers is an important indicator of child health influenced by socioeconomic factors and dietary patterns. The study was aimed to analyze the relationship between family income level and dietary patterns with the nutritional status of toddlers. The research employed a quantitative method with a cross-sectional design and a descriptive correlational approach. The sample consisted of 58 toddlers determined using the slovin formula. The variables measured included family income level and dietary patterns as independent variables and nutritional status of toddlers as the dependent variable. Data were collected through structured questionnaires and anthropometric measurements. The results showed that the majority of families had low income (94.8%), and many toddlers had moderate dietary patterns (55.2%). The nutritional status of toddlers was categorized into good nutrition (43.1%), undernutrition (41.4%), and severe malnutrition (15.5%). Statistical analysis using the chi-square test indicated that there was no significant association between family income and the nutritional status of toddlers (p=0.623), and no significant association between dietary patterns and nutritional status (p=0.774). In conclusion, the nutritional status of toddlers is not only influenced by family income and dietary patterns, but also by other factors such as parenting practices, nutritional knowledge, and environmental conditions. It is recommended to improve parental nutrition education, enhance feeding practices, and strengthen health programs as well as integrative environmental interventions to improve the nutritional status of toddlers. Status gizi balita merupakan indikator penting kesehatan anak yang dipengaruhi oleh faktor sosial ekonomi dan pola makan. Penelitian ini bertujuan untuk menganalisis hubungan antara tingkat pendapatan keluarga dan pola makan dengan status gizi balita. Penelitian ini menggunakan metode kuantitatif dengan desain cross-sectional serta pendekatan deskriptif korelasional. Sampel penelitian terdiri dari 58 balita yang ditentukan menggunakan rumus Slovin. Variabel yang diukur meliputi tingkat pendapatan keluarga dan pola makan sebagai variabel independen serta status gizi balita sebagai variabel dependen. Data dikumpulkan melalui kuesioner terstruktur dan pengukuran antropometri. Hasil penelitian menunjukkan bahwa sebagian besar keluarga memiliki pendapatan rendah (94,8%), dan sebagian besar balita memiliki pola makan sedang (55,2%). Status gizi balita dikategorikan menjadi gizi baik (43,1%), gizi kurang (41,4%), dan gizi buruk (15,5%). Analisis statistik menggunakan uji chi-square menunjukkan bahwa tidak terdapat hubungan yang signifikan antara pendapatan keluarga dengan status gizi balita (nilai p=0,623), serta tidak terdapat hubungan yang signifikan antara pola makan dengan status gizi (nilai p=0,774). Kesimpulan, status gizi balita tidak hanya dipengaruhi oleh pendapatan keluarga dan pola makan, tetapi juga faktor lain seperti pola asuh pengasuhan, pengetahuan gizi dan kondisi lingkungan. Disarankan perlu peningkatan edukasi gizi kepada orang tua, perbaikan pola asuh dalam pemberian makan anak, serta dukungan program kesehatan dan perbaikan lingkungan secara terpadu guna meningkatkan status gizi balita.